Passive Tumor Targeting of Polymer Therapeutics: In Vivo Imaging of Both the Polymer Carrier and the Enzymatically Cleavable Drug Model - Pola, Robert; Heinrich, Anne-Kathrin; Mueller, Thomas; Kostka, Libor; Mäder, Karsten; Pechar, Michal; Etrych, Tomas (Macromolecular bioscience, 2016)
The enzymatic release of a model drug from a polymer carrier inside a tumor using multispectral optical imaging in vivo in nude mice bearing colorectal carcinomas HT-29 and DLD-1 is demonstrated. Much higher release rate in vivo from a linear (30 kDa) (N-2-hydroxypropyl)methacrylamide-based polymer compared with a high molecular weight branched (170 kDa) polymer conjugate is observed, probably due to steric hindrance of the cleavable spacer of the latter polymer to proteolytic enzymes. There is no significant difference in the relative biodistribution of the two polymers, but the branched polymer circulates much longer. Both polymers are labeled with two different fluorophores. Dyomics-676 as a drug model is attached to the polymer via an enzymatically cleavable Gly-Phe-Leu-Gly spacer; Dyomics 782 is bound to the same polymer via a nondegradable amide bond, enabling the tracking of the polymer carrier after i.v. application to mice.
Keywords: nosiče léků; fluorescenční barviva; Drug Carriers; Xenograft Model Antitumor Assays; akrylamidy; EPR effect; in vivo imaging; kolorektální nádory; tumor targeting; Fluorescent Dyes; Colorectal Neoplasms; Mice; Acrylamides; enzymatic release; Mice, Nude; xenogenní modely - testy protinádorové aktivity; zvířata; Humans; myši nahé; polymer drug carriers; myši; lidé; Animals